Lifestyle and perceived health in subjects with chronic bronchitis or emphysema: a cross-sectional study - Vukovic, Dejana S (BioMed Central, 2010)
BACKGROUND: The study aim was to compare lifestyle behaviors, body mass index (BMI) and perceived health in subjects with and without chronic bronchitis or emphysema, and to explore if these comparisons differed between demographic subgroups. METHODS: A stratified two-stage sample of the population of Serbia was used; 14.522 adults aged ≥20 years were interviewed. RESULTS: Compared with controls, respondents with chronic bronchitis or emphysema reported a 23% increased likelihood of eating fresh vegetables every day (CI 1.02-1.48), 58% increased likelihood of currently smoking (CI 1.32-1.88) and more likely to perceive their health as very bad or bad (OR 4.67, CI 3.64-5.98). After stratification for sex, education, and type of settlement, smoking was significantly associated with chronic bronchitis or emphysema in all subgroups except males. The increased likelihood of very bad or bad perceived health in respondents with chronic bronchitis or emphysema was significant in all subgroups, and was highest for respondents ≤65 years of age (adjusted OR 6.51; CI 4.87-8.72) and lowest for respondents >65 years of age (adjusted OR 3.25; CI 2.12-4.97). CONCLUSION: Efforts to enhance perceived health and healthy lifestyle behaviors in subjects with chronic bronchitis or emphysema are necessary. Special attention should be paid to smoking cessation in almost all demographic subgroups.